ChemInform Abstract: Diastereoselective Fluorocyclopropanation of Chiral Allylic Alcohols Using an α‐Fluoroiodomethylzinc Carbenoid. Issue 5 (January 2016) - Navuluri, Chandrasekhar; Charette, Andre B.
Abstract: A highly diastereoselective fluorocyclopropanation of allylic alcohols (I), (IV), and (VI) and glyceraldehyde derived allylic ethers (VIII) and (X) is developed using fluorocarbenoid (II) as methylene source.